2017
DOI: 10.1055/s-0043-119635
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Affects Adipose Tissue-Derived Mesenchymal Stem Cell Aging Through TERT Gene Expression

Abstract: Aging and losing cell survival is one of the main problems in cell therapy. Aging of Mesenchymal Stem Cells (MSCs) is associated with a rise in intracellular reactive oxygen species, decrease in telomerase reverse transcriptase (TERT) expression and finally eroded telomere ends. Given that the production of free radicals in the aging process is effective, the use of antioxidants can help in scavenging free radicals and prevent the aging of cells. The aim of this study is to evaluate the effects of curcumin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…The mechanisms of functional decline of ASCs at expansion conditions are not clear. The study by Li et al, revealed that MSCs changes are in both gene expression and epigenetic levels represented with reduced expression of stemness genes including Oct-4 and Sox2, along with dysregulations of histone acetylation [8], reduced proliferation potential, some phenotypic changes, tendency for spontaneous differentiation, and aging [9]. Since genetic manipulations of stem cells is not always possible and may raise some risks for clinical applications, using the epigenetic mechanisms for maintaining self-renewal and stemness properties is ideal.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of functional decline of ASCs at expansion conditions are not clear. The study by Li et al, revealed that MSCs changes are in both gene expression and epigenetic levels represented with reduced expression of stemness genes including Oct-4 and Sox2, along with dysregulations of histone acetylation [8], reduced proliferation potential, some phenotypic changes, tendency for spontaneous differentiation, and aging [9]. Since genetic manipulations of stem cells is not always possible and may raise some risks for clinical applications, using the epigenetic mechanisms for maintaining self-renewal and stemness properties is ideal.…”
Section: Resultsmentioning
confidence: 99%
“…ACR intoxication signi cantly reduced the expression of TERT in the brain, suggesting the TERT-related anti-apoptotic function participated in the ACR neurotoxicity [5]. Interestingly, some new evidences showing that curcumin up-regulates function of TERT have emerged [27,28]. Curcumin extracted with ethyl acetate concentration-dependently upregulated the TERT mRNA expression in rat clone-9 hepatocytes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin extracted with ethyl acetate concentration-dependently upregulated the TERT mRNA expression in rat clone-9 hepatocytes [27]. Pirmoradi et al [28] reported that the TERT expression of rat adipose tissue-derived stem cells was signi cantly increased in the presence of curcumin at concentrations of 1 and 5 µM. In line with these in vitro studies [27,28], we showed the curcumin-induced in vivo up-regulation of TERT at the levels of gene and protein, which might be one mechanism underlying the anti-apoptotic activity of curcumin in ACR-intoxicated brains.…”
Section: Discussionmentioning
confidence: 99%
“…Shailaja et al [220] showed that curcumin could reduce the level of C-reactive protein (CRP) and enhance the level of malondialdehyde (MDA), which play a favorable role in slowing aging by inhibiting the expression of age-related inflammatory cytokines. By using concentrations of 1 μM, 5 μM, 10 μM, and 20 μM, Pirmoradi et al [221] found the intervention effect of curcumin in rat adipose tissue-derived stem cells (rADSC) in vitro. Their results showed that curcumin could promote the proliferation of rADSC and reduce the senescence of adipose stem cells by promoting TERT gene expression.…”
Section: 22mentioning
confidence: 99%